Advancements in CAR-NK therapy: lessons to be learned from CAR-T therapy - Kilgour, Marisa K.; Bastin, Donald J.; Lee, Seung-Hwan; Ardolino, Michele; McComb, Scott; Visram, Alissa (Frontiers in Immunology, 2023)
Advancements in chimeric antigen receptor engineered T-cell (CAR-T) therapy have revolutionized treatment for several cancer types over the past decade. Despite this success, obstacles including the high price tag, manufacturing complexity, and treatment-associated toxicities have limited the broad application of this therapy. Chimeric antigen receptor engineered natural killer cell (CAR-NK) therapy offers a potential opportunity for a simpler and more affordable “off-the-shelf” treatment, likely with fewer toxicities. However, the development of CAR-NK therapies is still early in development. Given the challenges experienced through the development of CAR-T therapies, this review explores what lessons we can apply to build better CAR-NK therapies. In particular, we explore the importance of optimizing the immunochemical properties of the CAR construct, understand factors leading to cell product persistence, enhancing trafficking of transferred cells to the tumor, ensuring the metabolic fitness of the transferred product, and strategies to avoid tumor escape through antigen loss. We review trogocytosis which is also an important emerging challenge that likely equally applies to CAR-T and CAR-NK cells. Finally, we discuss how these limitations are already being addressed in CAR-NK therapies, and what future directions may be possible.